Comparative Prognostic Value of Podocyturia Versus Microalbuminuria in Predicting Diabetic Nephropathy Progression: A Meta-Analysis - Bayu Arief Hartanto; Deka Viotra; Harnavi Harun; Drajad Priyono (HM Publisher, 2026)
Background: Diabetic nephropathy represents the primary etiology of end-stage renal disease globally. Historically, clinical practice relied upon microalbuminuria as the definitive non-invasive biomarker for early detection. However, advanced histopathological evidence establishes that severe structural degradation of the glomerular filtration barrier, specifically the visceral epithelial cells known as podocytes, occurs significantly earlier than the clinical manifestation of microalbuminuria. Podocyturia, defined as the urinary excretion of intact podocytes and podocyte-specific proteins or messenger RNA, emerged as a direct indicator of active glomerular injury. This meta-analysis investigated the comparative prognostic value of podocyturia versus microalbuminuria in predicting the longitudinal progression of diabetic nephropathy. Methods: A systematic literature search was executed to identify comparative clinical studies evaluating both podocyturia and microalbuminuria in diabetic cohorts. Seven essential manuscripts met rigorous inclusion criteria. Following peer-review recommendations, statistical pooling was strictly stratified by study design. Data extraction focused on prognostic effect sizes in longitudinal cohorts and diagnostic effect sizes in cross-sectional cohorts. Statistical synthesis utilized DerSimonian-Laird random-effects models to calculate pooled Standardized Mean Differences and 95% confidence intervals. Results: Synthesized data demonstrated podocyturia possessed a significantly superior prognostic value compared to microalbuminuria. In longitudinal cohorts, the pooled Standardized Mean Difference for podocyturia predicting progression was 1.95 (95% CI: 1.50 to 2.40, p < 0.001), whereas microalbuminuria was 0.58 (95% CI: 0.25 to 0.91, p = 0.04). Cross-sectional data similarly demonstrated massive podocyte biomarker elevation in strictly normoalbuminuric patients. Conclusion: Podocyturia represents a substantially more accurate, sensitive, and temporally earlier prognostic biomarker for diabetic nephropathy progression than microalbuminuria. Incorporating podocyte-specific urinary quantification into routine clinical practice could fundamentally alter early therapeutic intervention strategies, shifting the focus toward arresting primary podocyte detachment.